Integrasi Nilai-nilai Tauhid pada Pelajaran Sains bagi Siswa Sekolah Dasar Islam Terpadu - Hasan Basri (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Abstract The development of Islamic education in Indonesia was marked by the emergence and growth of Integrated Islamic schools. The term ‘integrated’ existed in order to counter the dichotomous education mindset. One example of such integrated schools is NurulIshlah Integrated Islamic Primary School (SD IT Nurul Ishlah), an alternative educational institution that combines various disciplineswith religion in order to eradicate the dichotomy in science. This study aimed to investigate the model, strategy, and obstacles of the integration of tawheed (monotheistic) values in the science lesson about the solar system. The study was a qualitative study, with the object of study being the integration of tawheed values in science lessons at SD IT NurulIshlah Banda Aceh. Data were collected by observation, interview, and documentation. The analysis was done by interpreting the collected data from which the conclusions were drawn.The results of the study showed that the integration of tawheed values in science learning about the solarsystemused the integrated model, as both kauniyah (natural phenomena) and qauliyah (the Qur’an) aspects were combined. The integration also employed several strategies during learning, including lecture, question and answer, assignment (recitation), discussion, and group work. On the other hand, the integration faced some obstacles in science learningwhich further became a reflection for the science teachers, such as the difficulty in finding thetawheed values that were truly relevant with the scientific concepts or materials, especially about the solarsystem, even though each teacher has been provided with examples of integrated Qur’anic and Hadith values from the educator team.